Sludge Coca-Cola untuk Penambahan Formula Bahan Baku Kompos - ARTHAGAMA, I DEWA MADE; DANA, I MADE (Agrotrop : Journal on Agriculture Science; Vol 12 No 2 (2022), 2022)
Coca-Cola Sludge For Adding Compost. This study aims to determine the compost formula with the addition of Coca-cola sludge to improve the quality of the compost. This research was conducted from June to July 2021, using a completely randomized design (CRD) consisting of 11 formulations of compost material, namely: A = (3 kg cow manure + 1 kg rice straw + 0 kg Coca-cola sludge); B = (2.5 kg cow manure + 1.5 kg rice straw + 0.5 kg Coca-cola sludge); C = (2 kg cow manure + 2 kg rice straw + 1 kg Coca-cola sludge); D = (1.5 kg cow manure + 2.5 kg rice straw + 1.5 kg Coca-cola sludge); E = (1 kg cow manure + 3 kg rice straw + 2 kg Coca-cola sludge); F =( 0.5 kg cow manure + 3.5 kg rice straw + 2.5 kg Coca-cola sludge); G =(2.5 kg goat manure + 1.5 kg rice straw + 0.5 kg Coca-cola sludge); H =(2 kg goat manure + 2 kg rice straw + 1 kg Coca-cola sludge); I =(1.5 kg goat manure + 2.5 kg rice straw + 1.5 kg Coca-cola sludge); J =(0.5 kg goat manure + 3.5 kg rice straw + 2.5 kg Coca-cola sludge); K = (3 kg Goat manure + 1 kg rice straw + 0.5 kg Coca-cola sludge). Each treatment was repeated 3 times so that 33 experiments were obtained.The results showed that treatment G = (2.5 kg goat manure + 1.5 kg rice straw + 0.5 kg Coca-cola sludge) gave the best compost quality as indicated by the highest N, P, and K parameter values, the best C/N ratio, and pH is close to neutral.  It should be tried to be applied in the field for plant growth and production.